تقرير الأهداف الإنمائية للألفية 2015 - United Nations Department of Economic; Social Affairs (United Nations, 2016)
The report presents the yearly assessment of global progress towards the Millennium Development Goals (MDGs), determining the areas where progress has been made, and those that are lagging behind. The report is based on a master set of data compiled by the Inter-Agency and Expert Group on MDG indicators led by the Statistics Division of the Department of Economic and Social Affairs.